Eco-Guard: Innovative Herbal Antidotes for Mosquito Control - Divya Lakshmi.S,; Sharmi.R,; Shalini.S,; Aafreen Fathima. T,; Abirami. M, (The Bioscan, 2024)
Mosquitoes pose a significant threat to human health as vectors of diseases such as malaria, filariasis, Japanese encephalitis, dengue fever, chikungunya, and yellow fever. Conventional mosquito control methods, including chemical liquid vaporizers and synthetic insecticides, can cause ecological imbalances, environmental pollution, and harm to non- target organisms. Additionally, these methods can be prohibitively expensive for those living below the poverty line. Therefore, safer and more biodegradable alternatives are necessary. This research explores the use of plant extracts as a natural and effective mosquito repellent. Citrus peel extract, containing bioactive chemicals such as alkaloids, flavonoids, tannins, and phenolic compounds, disrupts the host-seeking ability of mosquitoes by impacting their nervous system. The scent of citrus affects mosquito behaviour and leads to neural collapse upon contact. Artemisia pallens, known for its antimicrobial properties and pleasant fragrance, is also employed. Moreover, A. calamus rhizome exhibits a variety of pharmacological responses, including sedative, CNS depressant, anticonvulsant, antispasmodic, cardiovascular, hypolipidemic, immunosuppressive, anti-inflammatory, cryoprotective, antioxidant, antidiarrheal, antimicrobial, anticancer, and antidiabetic activities. The study discusses the ethanol extraction process of these plant materials to develop an effective mosquito repellent. By utilizing these natural ingredients, we aim to provide an affordable, non- hazardous, and environmentally friendly alternative to synthetic insecticides (4). This herbal mosquito repellent not only offers immediate relief from mosquito bites but also holds potential for broader applications as a general insecticide. The findings underscore the importance of integrating traditional botanical knowledge with modern scientific approaches to address global health challenges posed by mosquitoes. Further research is warranted to optimize the formulation and expand its use against other insect pests.